THE INTER-ORGANIZATIONAL NETWORK MANAGEMENT MODEL AND THE DIFFUSION OF INFORMATION - Gródek-Szostak, Zofia; Kajrunajtys, Danuta; Ochoa Siguencia, Luis; Chęcińska-Kopiec, Agnieszka (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Contemporary companies are looking for opportunities to stay in the market in the long run. They invest a great effort in this purpose and create logical concepts for joint business activities, which take the form of inter-organizational networks. The challenge is to manage such a defined whole, as well as to provide information for decision-making. To streamline management, it is necessary to organize and manage the information flow in the network. The purpose of this paper is to outline the authors' approach to the design of an information flow in an inter-organizational network that takes into account the requirements of network managers. The starting point is to develop a common vision of the network’s business model. On this basis, the functionality of the information subsystem should be defined.